Promising antioxidant and anticancer (human breast cancer) oxidovanadium(IV) complex of chlorogenic acid. Synthesis, characterization and spectroscopic examination on the transport mechanism with bovine serum albumin - Naso, Luciana Gissella (2014)
A new chlorogenate oxidovanadium complex (Na[VO(chlorog)(H 2O)3].4H2O) was synthesized by using Schlenk methodology in the course of a reaction at inert atmosphere in which deprotonated chlorogenic acid ligand binds to oxidovanadium(IV) in a reaction experiment controlled via EPR technique and based in a species distribution diagram. The compound was characterized by FTIR, EPR, UV-visible and diffuse reflectance spectroscopies and thermogravimetric, differential thermal and elemental analyses. The ligand and the complex were tested for their antioxidant effects on DPPH (1,1-diphenyl-2-picrylhydrazyl radical), ABTS+ (radical cation of 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt), O2-, OH and ROO radicals and their cytotoxic activity on different cancer cell lines (SKBR3, T47D and MDAMB231) and primary human mammary epithelial cells. The complex behaved as good antioxidant agent with strongest inhibitory effects on O2-, OH and ROO radicals and exhibited selective cytotoxicity against SKBR3 cancer cell line. Albumin interaction experiments denoted high affinity toward the complex and its calculated binding constant was indicative of a strong binding to the protein. Based on this study, it is hypothesized that Na[VO(chlorog)(H 2O)3].4H2O would be a promising candidate for further evaluation as an antioxidant and anticancer agent.